2020
DOI: 10.1101/2020.08.25.20154252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 RNA viremia is associated with a sepsis-like host response and critical illness in COVID-19

Abstract: Background: Severe COVID-19 is characterized by clinical and biological manifestations typically observed in sepsis. SARS-CoV-2 RNA is commonly detected in nasopharyngeal swabs, however viral RNA can be found also in peripheral blood and other tissues. Whether systemic spreading of the virus or viral components plays a role in the pathogenesis of the sepsis like disease observed in severe COVID-19 is currently unknown. Methods: We determined the association of plasma SARS-CoV-2 RNA with the biological response… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 50 publications
0
55
2
Order By: Relevance
“…In our study, RNAemia was more frequent in ICU patients with type 2 diabetes and hypertension, two well-known risk factors for poor outcome in COVID-19. Using droplet digital PCR 15 RNAemia could be a consequence of severe disease or might contribute to poor outcome. Given that the SARS-CoV-2 entry receptor ACE2 is expressed on vascular cells, including endothelial cells, smooth muscle cells and pericytes of most organs 38,39 , and SARS-CoV-2 RNA was detected in lungs, pharynx, heart, liver, brain and kidneys of autopsy tissue 40 Furthermore, binding of C1q to NETs protects NETs from degradation by DNases in the circulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, RNAemia was more frequent in ICU patients with type 2 diabetes and hypertension, two well-known risk factors for poor outcome in COVID-19. Using droplet digital PCR 15 RNAemia could be a consequence of severe disease or might contribute to poor outcome. Given that the SARS-CoV-2 entry receptor ACE2 is expressed on vascular cells, including endothelial cells, smooth muscle cells and pericytes of most organs 38,39 , and SARS-CoV-2 RNA was detected in lungs, pharynx, heart, liver, brain and kidneys of autopsy tissue 40 Furthermore, binding of C1q to NETs protects NETs from degradation by DNases in the circulation .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, circulating SARS-CoV-2 RNA (RNAemia) has been highlighted as a promising prognostic biomarker in hospitalized COVID-19 patients, as it is associated with disease severity 7 and mortality [8][9][10] , with an estimated prevalence of 10% (95% CI 5-18%, random effects model) 7 . Further, we hypothesized that the acute and profound alterations in the innate and adaptive immune system in COVID-19 patients 3,[11][12][13] , especially in RNAemic patients [14][15][16][17][18] , will be accompanied by marked changes in the circulating proteome and interactome and that the proteome in COVID-19 patients will highlight mechanistically relevant signatures and trajectories, when compared to non-COVID-19 sepsis and healthy controls. Thus far, proteomics studies have focused on the determination of protein biomarkers of COVID-19 severity [19][20][21][22] , but have not assessed the longitudinal relationship between proteomic changes, RNAemia and 28-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Although the COVID-19 pandemic has been ongoing now for several months, very little attention has been given to mucosal immunity in SARS-CoV-2 infection. Yet this virus primarily infects the mucosal surfaces of the respiratory tract (and possibly also the digestive tract) at least until advanced stages of the disease when viral RNA may become detectable in the circulation (1). The virus may also be acquired through the mouth, and at the conjunctival surface of the eye whence it drains into the nasal passages through the lacrimal duct.…”
Section: Introductionmentioning
confidence: 99%
“…19 Two cross-sectional studies using droplet-based dPCR reported higher rates of RNAaemia (42•4% and 74•1%) than did the qPCR studies above, and associated the presence and the level of RNAaemia with clinical severity. 8,9 Bermejo-Martin et al also observed correlation between RNAaemia and biomarkers of dysregulated host responses. 8 In this prospective, longitudinal, observational study of COVID-19 patients presenting to the Emergency Department (ED), we characterised relationships between SARS-CoV-2 RNAaemia and overall severity, clinical deterioration, and specific EPCs.…”
mentioning
confidence: 97%
“…8,9 Bermejo-Martin et al also observed correlation between RNAaemia and biomarkers of dysregulated host responses. 8 In this prospective, longitudinal, observational study of COVID-19 patients presenting to the Emergency Department (ED), we characterised relationships between SARS-CoV-2 RNAaemia and overall severity, clinical deterioration, and specific EPCs. We used an array-based dPCR platform to maximise reliability and replicability, and to simplify potential clinical adoption of RNAaemia testing.…”
mentioning
confidence: 97%